1980
DOI: 10.1126/science.7403859
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Selectively Inhibits Growth of Human Cancer Cells

Abstract: The growth of human cancer cells from lung, breast, and uterine tumors was selectively inhibited in a dose-dependent manner by ozone at 0.3 to 0.8 part per million of ozone in ambient air during 8 days of culture. Human lung diploid fibroblasts served as noncancerous control cells. The presence of ozone at 0.3 to 0.5 part per million inhibited cancer cell growth 40 and 60 percent, respectively. The noncancerous lung cells were unaffected at these levels. Exposure to ozone at 0.8 part per million inhibited canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 12 publications
2
56
0
Order By: Relevance
“…We did not see significant change in cell death in control culture which is not treated with ozone. Similar kind of response was observed in human cancer cell treated with ozone where treatment of ozone caused 40-60% cell death [8].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We did not see significant change in cell death in control culture which is not treated with ozone. Similar kind of response was observed in human cancer cell treated with ozone where treatment of ozone caused 40-60% cell death [8].…”
Section: Discussionsupporting
confidence: 62%
“…In 1980 laboratory studies by main stream cancer researchers at Washington University discovered that the growth of human cancer cells from lung, breast, and uterine tumors was selectively inhibited in a dosedependent manner by ozone at 0.3 to 0.8 part per million of ozone in ambient air during 8 days of culture. Human lung diploid fibroblasts served as noncancerous control cells [8]. In 1990 preclinical French studies reported ozone enhanced the treatment of chemo resistant tumors and seemed to act adjunctively to chemotherapy in tumors derived from the colon and breast [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone, which can also produce oxygen free radicals, selectively inhibits growth of human cancer cells in comparison to normal cells [28]. Indeed, many of the anticancer drugs appear to generate the superoxide or hydroxyl radicals when activated appropriately .…”
Section: Discussionmentioning
confidence: 99%
“…In 1980 Sweet et al presented the evidence of ozone inhibiting effect relative to tumor cells in vitro, having found a weak ability of these cells to compensate the oxygen "burst" caused by ozone in comparison with normal cells, and estimated 90% suppression of malignant cell growth [1].…”
mentioning
confidence: 99%